Potential for increased photosynthetic performance and crop productivity in response to climate change: role of CBFs and gibberellic acid - Hüner, Norman P. A.; Dahal, Keshav; Kurepin, Leonid V.; Savitch, Leonid; Singh, Jas; Ivanov, Alexander G.; Kane, Khalil; Sarhan, Fathey (Frontiers in Chemistry, 2014)
We propose that targeting the dwarf phenotype, enhanced photosynthetic performance typically associated with the cold acclimation of winter cultivars of rye (Secale cereale L.), wheat (Triticum aestivum L.) and Brassica napus L. may provide a novel approach to improve crop yield and productivity under abiotic as well as biotic stress conditions. In support of this hypothesis, we provide the physiological, biochemical and molecular evidence that the dwarf phenotype induced by cold acclimation is coupled to significant enhancement in photosynthetic performance, resistance to photoinhibition and a decreased dependence on photoprotection through nonphotochemical quenching which result in enhanced biomass production and ultimately increased seed yield. These system-wide changes at the levels of phenotype, physiology and biochemistry appear to be governed by the family of C-repeat / dehydration-responsive family of transcription factors (CBF/DREB1). We relate this phenomenon to the semi-dwarf, gibberellic acid insensitive, cereal varieties developed during the “green revolution” of the early 1960s and 1970s. We suggest that genetic manipulation of the family of C-repeat / dehydration-responsive element binding transcription factors (CBF/DREB1) may provide a novel approach for the maintenance and perhaps even the enhancement of plant productivity under conditions of sub-optimal growth conditions predicted for our future climate.